Computer simulation of natural light in different brazilian bioclimatic zones - Nascimento, Jéssica Wanderley Souza do; Sampaio, Allefy Teles; Schuster, Sílvio Lisbôa; Santos, Sabiana Gilsane Mühlen dos; Umbelino, Mariana Ferreira; Sales, Hugo Leonardo Menezes de (Brazilian Journal of Production Engineering, 2024)
Natural lighting, when present in the internal environments of buildings, in accordance with the needs of each location, brings benefits to human health. On the other hand, when it is at odds with the space, it can have a negative effect, causing problems such as glare, reflections, shadows and thermal interference. In this context, this research aims to simulate, interpret and compare how natural light and its luminous performance, based on the sDA (Spatial Daylight Autonomy) metric, behave in a residential environment in the cities of Santa Maria/RS (bioclimatic zone 2), Cuiabá/MT (bioclimatic zone 7) and Fortaleza/CE (bioclimatic zone 8). DesignBuilder software was used, taking into account the criteria adopted by the RTQ-R for more detailed analytical processing of the data. The results obtained in the simulations indicate that the best-performing natural light indices in the models analyzed in the 300 lux range reached 99.52% and were positioned on the west façade of the city of Cuiabá/MT, while the worst-performing indices reached 57.49% and were simulated on the south façade of the city of Santa Maria/RS. This is due to the fact that, in the Southern Hemisphere, the north and west façades receive more direct sunlight than the south and east façades.
Keywords: Energy efficiency; Metrics; Simulation